Business Models as an Adaptation Strategy for MSMEs in Responding to Changes in the Business Environment: a Conceptual Perspective - Sarah Sakiran Salsabila; Khoirul Ilmiyati; Agung Winarno; Heny Kusdiyanti (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
The rapidly changing and increasingly uncertain business environment presents significant challenges for micro, small, and medium enterprises (MSMEs), requiring them to adapt quickly and strategically to survive and remain competitive. This conceptual article examines the role of business models as an effective adaptation strategy for MSMEs in responding to dynamic market conditions, technological change, and shifting consumer preferences. Through a comprehensive review of various business model frameworks and dynamic capability theories, this study emphasizes that business models play a crucial role in shaping organizational flexibility and strategic responsiveness. The findings highlight that adaptable value propositions enable MSMEs to continuously align their offerings with evolving customer needs, while agile resource management allows firms to efficiently reconfigure internal and external resources. Furthermore, continuous business model innovation and renewal are identified as essential mechanisms for sustaining long-term resilience and competitiveness. The article argues that a business model should not be viewed merely as an operational or administrative tool, but rather as a core strategic mechanism that integrates strategic vision, organizational capabilities, and market orientation. By actively leveraging flexible and innovative business models, MSMEs can enhance their adaptive capacity, mitigate environmental uncertainty, and achieve sustainable competitive advantage in rapidly changing business environments.